2018
DOI: 10.3390/nu11010008
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Patterns Related to Triglyceride and High-Density Lipoprotein Cholesterol and the Incidence of Type 2 Diabetes in Korean Men and Women

Abstract: We aimed to examine whether dietary patterns that explain the variation of triglyceride (TG) to high-density lipoprotein cholesterol (HDL-C) ratio were associated with the incidence of type 2 diabetes in Korean adults. We included a total of 5097 adults without diabetes at baseline with a mean follow-up of 11.54 years. Usual diet was assessed by a validated food frequency questionnaire, and serum levels of TG and HDL-C were measured at baseline. We derived dietary pattern scores using 41 food groups as predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 50 publications
1
22
0
Order By: Relevance
“…As validated by a Chinese population-based study, environmental tobacco exposure increased T2DM risks with a dose-response relationship (36), which also verified our results laterally. Higher HDL-c and lower TG levels were associated with lower risks of T2DM prevalence in both genders in our research (Table 2), which were consistent with other studies (37,38). A nationwide population-based study in Korea enrolling 5,114,735 adults with a median follow-up period of 5.1 years had found that lower means of HDL-C were associated with higher risks of diabetes incidence in a stepwise manner (39).…”
Section: Discussionsupporting
confidence: 91%
“…As validated by a Chinese population-based study, environmental tobacco exposure increased T2DM risks with a dose-response relationship (36), which also verified our results laterally. Higher HDL-c and lower TG levels were associated with lower risks of T2DM prevalence in both genders in our research (Table 2), which were consistent with other studies (37,38). A nationwide population-based study in Korea enrolling 5,114,735 adults with a median follow-up period of 5.1 years had found that lower means of HDL-C were associated with higher risks of diabetes incidence in a stepwise manner (39).…”
Section: Discussionsupporting
confidence: 91%
“…T2DM is a metabolic disease characterized by hyperglycemia and caused by relatively insufficient insulin secretion or insulin resistance (2). However, the pathogenesis of T2DM is complicated, including heredity, lifestyle, environmental, as well as unknown factors (3). Some studies have indicated that intestinal flora disorders can mediate the occurrence of T2DM, particularly those inducing insulin resistance by regulating visceral adipose tissue (VAT) inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from evaluating the association between micronutrients and the risk of type 2 diabetes, the role of macronutrients and other metabolites in the development of this condition have been studied extensively. Song et al [15] sought to examine whether dietary patterns that explain the variation of the triglyceride (TG) to high-density lipoprotein cholesterol (HDL-C) ratio were associated with the incidence of type 2 diabetes in Korean men and women. The authors found evidence that suggests that dietary patterns associated with low levels of TG/HDL-C ratio may have the potential to reduce the risk of type 2 diabetes.…”
mentioning
confidence: 99%